Clinical and serological findings for atypical respiratory infections in asthmatic children in Grau Emergency Hospital, EsSalud, 2007 - Huamaní Egocheaga, Rómulo (2009)
Objective: The objective of this study was to determine the profile of infections caused by atypical microorganisms in children with asthma exacerbations treated in Grau Emergency Hospital during 2007. Methodology: This is a prospective and cross-sectional study performed in 2007, in which 90 patients between 2 and 14 years old who were brought to the Pediatric Emergency area because of asthma exacerbations refractyory to conventional therapy were included. A blood sample was taken from all patients, in order to perform an ELISA indirect immunoassay test, looking for IgM showing acute infections caused by Chlamydia pneumoniae and Mycplasma pneumoniae. Results: An overall prevalence of respiratory infections caused by atypical microorganisms was found in 30% (27/90) of children with asthma, 20% (18/90) for Chlamydia pneumoniae, 13.3% (12/90) for Mycoplasma pneumoniae, and mixed infections (M. pneumoniae and C. pneumoniae) in 3.3% (3/90). We also found that infections caused by atypical agents increased in winter (33.3%), while those caused by Chlamydia were prevalent all over the year. There were no significant differences in frequency of these infections with respet to age (being more or less than 5 years old) or sex. More frequent radiological featurees were peribronchial thickening (29.6%), chest hyperinflation (22.2%), and hilar opacities (22.2%). CBCs were reported as nromal in more than 80% of the patients (22/27). Conclusions: The overall prevalence of atypical microorganisms in children with asthma exacerbations was 30%, and it was independent of age and sex. We must have a high clinical suspicion index for theses conditions in children brought to the ER with history of persistant asthma withy moderate exacerbations refractory to conbventional therapy who also have a normal CBC and a chest X-ray pattern showing peribronchiaal thickening, chest hyperinflation, and hilar opacities.